Chemotherapy-Induced Nausea and Vomiting in Gastrointestinal Cancer Patients: Do We Need to Revisit Guidelines? - Kapoor, Akhil; Jain, Ashutosh; Sharma, Abhishek; Shah, Minit; Chinthala, Shravan; Nandhana, Ravindra; Bhargava, Prabhat; Ramaswamy, Anant; Srinivas, Sujay; Ostwal, Vikas (South Asian Journal of Cancer, 2020)
Purpose The objective of this study was to assess the proportion of patients developing chemotherapy-induced nausea and vomiting (CINV) after receiving chemotherapy for gastrointestinal (GI) cancers, despite receiving antiemetic prophylaxis (AEP) as per the standard guidelines.Patients and Methods Between April 2019 and March 2020, all patients planned for chemotherapy were eligible for enrolment in the study. The primary endpoint of the study was the assessment of complete response (CR) rates.Results Overall, 1,276 consecutive patients were screened for this study, while 738 patients fulfilling the eligibility criteria were included. A total of 23.2% of the whole cohort failed to achieve CR. Also, 28.2, 16.9, and 16.6% of patients receiving moderately emetogenic chemotherapy (MEC), low emetogenic chemotherapy (LEC), and high emetogenic chemotherapy (HEC), respectively, failed to achieve CR. The differences in failure to achieve CR was statistically significant between MEC and HEC (p < 0.001) groups. Among MEC group, there was no difference between those who received oxaliplatin (27.8%) versus nonoxaliplatin regimens (25.8%) in terms of failure rates (p = 0.613).Conclusion Approximately one-fourth of patients failed to achieve a complete response from CINV in GI cancers despite using guideline-based AEP. Patients receiving MEC had the highest failure rates suggesting a need to improve AEP in these patients.
Keywords: CINV; moderately emetogenic chemotherapy; MEC; oxaliplatin; complete response